Financial management : An assessment of access to Financial Management Services by Small, Medium and Micro Enterprises in Thohoyandou Business Centre (Thulamela Municipality) - Ndou, Muhali Piet (My University, 2010)
Small, Medium and Micro-Enterprises (SMMEs) as vehicles of growth, innovation and social transformation, are important categories of businesses which must be nurtured and harnessed by the South African authorities. This should enable them to quickly and effectively adapt to the challenges of globalization thereby benefiting the economy. The importance of SMMEs to the South African economy has already been acknowledged by government. Despite the growth in venture capital funding, access to funding remains a problem for small enterprises, in particular for empowerment groups in South Africa. In most surveys among small enterprises, the provision of concessionary finance comes out as one of the most urgently felt needs. Indeed extensive research reveals that access financing is one of the several important factors that are critical for business survival and growth while other factors are market access and lack of financial management skills. South Africa’s financial sectors have always been reluctant to provide comprehensive services for the fragmented, risk-prone and geographically dispersed small enterprises sector. Evidence of management skills and business knowledge are indications of how well an entrepreneur can perform important tasks and activities related to the eight functions of a business, which are: general management, operations, finance, purchasing, human resources,marketing, administration and external relations. One of the major hurdles that face entrepreneurial endeavours is the shortage of financial management skills. South Africa shows a grim picture of the skills gap. SMMEs become the hardest hit as the entire commerce sector forages for the scarcest skills. Small enterprises have been victims of instances of developing their employees only to lose them to bigger firms offering more lucrative incentives and currently SMMEs in South Africa’s expanding construction sector are losing the fight in the battle for scarce skills. Although government has tried to put in place policies and institutions with the aim of improving the accessing of finance by small business owners, their success has been minimal. It is, therefore, imperative that management capability and financial management acumen be regarded as key to accessing funding by the entrepreneurs themselves, and the parties involved in supporting and promoting them. It is important to bear in mind that training in entrepreneurial skills without training in business skills will not ensure optimal results. A combination of training to develop entrepreneurial skills and business training is most effective in preparing and developing successful entrepreneurs. Therefore, this study is an assessment on access to financial management services by SMMEs in Thohoyandou Business Centre, as funding has a bearing on the economic development and sustainability of SMMEs. The research wanted to establish if the SMMEs in Thohoyandou Business Centre had access to financial management services support and, if they have, are the SMMEs ready to receive these financial management services? The study revealed that the SMMEs do not possess financial management skills neither do they have access to financial management services although most of them acknowledged that there is a need for these skills for the success of their businesses. The lack of requisite bookkeeping and financial management skills results in most financial institutions being unwilling to provide funds to this sector, resulting in entrepreneurs relying on their own sources of finance which are limited as shown in the study. Management capability strengthens the financial capacity of SMMEs. Financial institutions are prone to be favourably biased towards SMMEs who can demonstrate eloquence in areas such as financial management (including basic bookkeeping), marketing and technology upgrading. It is recommended that government and other facilitators incorporate simplified components into their training packages to cover such areas as bookkeeping and compilation of business plans
Thesis (MBA) --University of Limpopo, 2010
Keywords: Financial management; Business enterprises finance; 338.642; Small business; Business enterprises -- South Africa -- Finance